2022
DOI: 10.1002/ange.202210334
|View full text |Cite
|
Sign up to set email alerts
|

Decarboxylative Selective Phosphorylation of Aliphatic Acids: A Transition‐Metal‐ and Photocatalyst‐Free Avenue to Dialkyl and Trialkyl Phosphine Oxides from White Phosphorus

Abstract: Developing practical and mild strategies for the direct functionalization of white phosphorus (P 4 ) without chlorination is an appealing but formidable challenge. To this end, we report a breakthrough in the preparation of structurally diverse dialkylphosphines and trialkylphosphines that rely on the successive generation of carbon-centered radicals from N-hydroxyphthalimide (NHPI) esters and the controllable alkylation of the P 4 molecule under transition-metal-and photocatalyst-free conditions. To facilitat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 87 publications
0
2
0
Order By: Relevance
“…12 Very recently, Tang et al reported the reaction of activated esters with P 4 under visible light to realize the synthesis of dialkyl and trialkyl phosphine oxides. 13 These two reactions involve the generation of radicals from preactivated substrates. In contrast, the generation of radicals from readily available halogenated hydrocarbons by photocatalytic reactions under mild conditions should be a good choice.…”
Section: ■ Introductionmentioning
confidence: 99%
“…12 Very recently, Tang et al reported the reaction of activated esters with P 4 under visible light to realize the synthesis of dialkyl and trialkyl phosphine oxides. 13 These two reactions involve the generation of radicals from preactivated substrates. In contrast, the generation of radicals from readily available halogenated hydrocarbons by photocatalytic reactions under mild conditions should be a good choice.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Recent advancements have been promising, with the development of safer, low-energy methods for synthesizing organophosphorus compounds. One such method involves directly functionalizing white phosphorus to convert it into phosphorus-containing chemicals without the use of chlorine [23][24][25][26][27][28][29][30] .…”
Section: Introductionmentioning
confidence: 99%
“…In 2019, we found the first photoredox method to synthesize phosphorotrithioites from thiols and P 4 (Scheme d) . Wolf et al conducted a pioneering study on the activation of P 4 by aryl radicals generated from readily available aryl halides under photoirradiation to access valuable triarylphosphines and tetraarylphosphonium salts (Scheme d). In 2022, we reported the facile functionalization of P 4 by alkyl radicals from N -hydroxyphthalimide (NHPI) esters to prepare structurally diverse dialkylphosphines and trialkylphosphines under visible-light irradiation without the need for an exogenous photoredox catalyst (Scheme d) …”
mentioning
confidence: 99%